From Pixels to Paragraphs: Exploring Enhanced Image-to-Text Generation using Inception v3 and Attention Mechanisms - Karaca, Zeynep; Das, Bihter (My University, 2023)
Processing visual data and converting it into text plays a crucial role in fields like information retrieval and data analysis in the digital world. At this juncture, the \"image-to-text\" transformation, which bridges the gap between visual and textual data, has garnered significant interest from researchers and industry experts. This article presents a study on generating text from images. The study aims to measure the contribution of adding an attention mechanism to the encoder-decoder-based Inception v3 deep learning architecture for image-to-text generation. In the model, the Inception v3 model is trained on the Flickr8k dataset to extract image features. The encoder-decoder structure with an attention mechanism is employed for next-word prediction, and the model is trained on the train images of the Flickr8k dataset for performance evaluation. Experimental results demonstrate the model's satisfactory ability to accurately perceive objects in images.
Keywords: Attention Mechanisms; Inception v3 Model; Textual Content Extraction; Image-to-Text Generation